Test-driven iOS development with Swift 4 : write Swift code that is maintainable, flexible, and easily extensible - Hauser, Dominik (Packt Publishing, 2017)
Use test-driven approach to develop highly-functional iOS apps with Swift 4 and Xcode 9 About This Book A practical guide to writing effective, organized, and clean code that works well Learn test-driven principles to help you build better-designed apps with fewer bugs A comprehensive overview of the techniques available for TDD in Swift Who This Book Is For To get the most out of this book, you will need some prior experience with Swift application development. You may have already heard about Test-Driven Development (TDD) but you don't need any prior experience of applying it to Swift applications. What You Will Learn Implement TDD in Swift application development Find bugs before you enter code using the TDD approach Use TDD to build models, view controllers, and views Test network code with asynchronous tests and stubs Write code that is a joy to read and maintain Develop functional tests to ensure the app works as planned In Detail Test-driven development (TDD) is a proven way to find software bugs early. Writing tests before you code improves the structure and maintainability of your apps. Using TDD, in combination with Swift 4's improved syntax, means there is no longer any excuse for writing bad code. This book will help you understand the process of TDD and how to apply it to your apps written in Swift. Through practical, real-world examples, you'll learn how to implement TDD in context. You will begin with an overview of the TDD workflow and then delve into unit-testing concepts and code cycles. You will also plan and structure your test-driven iOS app, and write tests to drive the development of view controllers and helper classes. Next, you'll learn how to write tests for network code and explore how the test-driven approach--in combination with stubs--helps you write network code even before the backend component is finished. Finally, the book will guide you through the next steps to becoming a testing expert by discussing integration tests, Behavior Driven Development (BDD), open source testing frameworks, and UI Tests (introduced in Xcode 9). Style and approach Using a step-by-step approach, you will develop an entire iOS app using TDD. During the course of the book, you will explore different strategies for writing tests for models, View Controllers, and networking code. Downloading the example code for this book. You can download the example code files for all Packt books you have purchased from your account at http://www.PacktP...